ANALISIS SIKAP ASERTIF KEBIJAKAN LUAR NEGERI CHINA DILAUT CHINA SELATAN PADA ERA XI JINPING - Fajrina Agharid, (2020)
China's Foreign Policy which always changes according to the needs of the Chinese state in order to achieve the National Interest of the Chinese. Since the leadership of Xi Jinping China has increasingly confirmed its claims in the South China Sea by showing its assertive policies in the South China Sea. Because according to Xi Jinping maintaining the sovereignty, security, and maintaining the territorial integrity it is a high priority of course this applies to the South China Sea area which they consider part of their territory, even though the claims they have made have clearly been rejected by UNCLOS. The researcher will analyze the assertive Chinese Foreign Policy in the South China Sea Area using Adaptive Foreign Policy, where the assertive policy can be analyzed from external, internal factors and also the attitude of the Chinese leader (Leadership). Researchers also use the Case Study method in this research approach. The transformation of assertive Chinese Foreign Policy in the Xi Jinping era towards the South China Sea region was due to certain factors that made China have to change its Foreign Policy, from external factors due to interference other than conflict countries, internal factors based on interests national China, and also Xi Jinping's way of leading a very strict and strong China to achieve his vision and mission while leading the country of China.